Characteristics Analysis Reveals the Progress of Volvariella volvacea Mycelium Subculture Degeneration - Chen, Xiao; Zhang, Zheng; Liu, Xiaoxia; Cui, Bo; Miao, Wentao; Cheng, Weiwei; Zhao, Fengyun (Frontiers in Microbiology, 2019)
Volvariella volvacea is a typical edible Basidiomycete with a high-temperature tolerance. It has a strong fibrinolysis capability and consumes abundant agricultural wastes. In agricultural cultivation, mycelial subculturing has been adopted, leading to serious strain degeneration. In this study, continuous mycelial subculturing of the common V. volvacea strain V971 (original strain recorded as M0) was performed in potato dextrose agar medium. One generation of the strain was preserved every 3 months (90 d); thus, six generations of degenerated strains (M1–M6) were obtained after 18 months of mycelial subculturing. The original and degenerated strains were preserved in sterile paraffin liquid at room temperature (18–25 °C). The biological traits and nutrients of M0 and M1–M6 were studied. The mycelial growth rate and biomass initially increased and then decreased as the degeneration progressed, reaching minimum levels of 0.041 ± 0.001 mm/h and 1.82 ± 0.25 g, respectively, at M6. Additionally, the polysaccharide, protein, polyphenol, flavone, total amino acid, and total mineral element contents of the strains decreased continuously, reaching minimum levels of 30.12 ± 3.12 g/100 g, 26.42 ± 2.1 g/100 g, 1.08 ± 0.05 g/100 g, 4.23 ± 0.21 g/100 g, 12.51 mg/g, and 398.05 mg/kg, respectively, at M6. The decolorization capability of V. volvacea in liquid medium supplemented with bromothymol blue and lactose reflected the degree of strain degeneration, with the capability weakening as the degeneration intensified. These results are highly significant for V. volvacea production. The mycelial characteristics during subculture-associated degeneration were described and provide an early identification method for V. volvacea’s degeneration.